BODY MASS INDEX, WAIST-HIP RATIO, AND FASTING BLOOD GLUCOSE LEVEL IN PRE-ELDERLY AT TANJUNG RAMBANG HEALTH CENTER OPERATING REGION - Yuliarti, Yuliarti; Febry, Fatmalina; Sari, Indah Purnama (Media Gizi Indonesia, 2025)
Elevated blood glucose when fasting is among the hazards associated with Diabetes Mellitus (DM). Obesity and diabetes mellitus are tightly associated. Body Mass Index (BMI) and Waist-Hip Ratio (WHR) measurements may be used to determine obesity. Prabumulih is known as city with a DM incidence of 2.02% in 2018, was placed second in South Sumatra. This research aims to investigate the relationship between BMI and WHR and older patient fasting blood glucose level in Tanjung Rambang Public Health Center operating region. Cross-sectional observational analysis is the method used in this study. The pre-elderly (45–59 years old) who resided in Tanjung RambangPublic Health Center working area made up as the population. Purposive sampling was used to choose 190 participants, meeting inclusion and exclusion criteria. This research use univariate and bivariate data analysis (using Chi Square test α=0.05). The majority of respondents (66.8%) are overweight; 53.2% of respondents had abnormal WHR; and 15.3% of respondents still had abnormal fasting blood glucose level. The analysis findings demonstrated no correlation (p=0.633) between BMI and fasting blood glucose level. The association between WHR and fasting blood glucose level is concluded to exist (p=0.001).